Sustainability of the Unsustainability. Its History and Sustainable Development - Picado, Wilson (2010)
In this paper we will take a look at the semantic history of the “sustainable development” concept through two significant aspects. First, we will review the history on the formation of the “development” concept, as a fundamental background to understand the origin of the public interest on the ecological problems underlying economic growth. Sec ondly, we will make a critical review about “sustainable development” from the point of view of its cyclic nature.